Instructional design and technological resources in the improvement of teachers' digital competencies - Miguel Ángel Losada Cárdenas; Claudia Cintya Peña Estrada (Universidad de Guadalajara, 2022)
This article presents an instructional design for strengthening competencies in the use of information and communication technologies, specifically in the dimension of digital resources. The ADDIE (analysis, design, development, implementation and evaluation) instructional design model was used; in addition, a virtual learning environment was implemented that allowed the development of synchronous-asynchronous sessions and the pedagogical elements around the training process. For the methodology, a designbased research was used with a non-probabilistic convenience sample composed of 32 elementary school teachers from Los Quindos institution, Colombia. Two research instruments were implemented: a Likert-type scale questionnaire for the analysis of teachers' social representations in the diagnostic phase, and a test that measures digital competencies according to the common European framework DigCompEdu. The application of the instructional model allowed the improvement of competence levels in all dimensions, constituting an innovative strategy in the educational field that favors interaction processes (collaborative learning) and autonomous learning.